Effect of pH, cationic inducer, and clam shells as bio-flocculant in the optimization of the flocculation process for enhanced microalgae harvesting using response surface methodology. Issue 1 (31st December 2022) - Hadiyanto, H.; Widayat, W.; Pratiwi, Monica Evanty; Christwardana, Marcelinus; Muylaert, Koenraad
ABSTRACT: Flocculants agglomerate suspended microalgae cells, while cost and toxicity have led to the increased use of bio-flocculants. In this experiment, Chlorella pyrenoidosa was gathered by utilizing bio-flocculants from discarded clam shells. At pH 8, 0.2 mg/mL of bio-flocculant clam shell, 0.1 mg/mL of cationic inducer, and 240 rpm of mixing achieved 91.87 % flocculation efficiency and 458.1 mg of recovered biomass. Calcium ions in bio-flocculants are the main contributor to Chlorella pyrenoidosa flocculation, employing charge neutralization and sweeping as flocculation mechanisms. Zn 2+ salt boosts flocculation by neutralizing the functional group's negative charge. The R 2 values of 0.8969 and 0.8894 for harvesting efficiency and recovered biomass reflect the model's predictive power. XRD exhibited faint, indistinct peaks with considerable noise, indicating that the chitosan bioflocculant did not have a crystalline structure and that Chlorella had become fibrillar. Response Surface Methodology approach, which promotes flocculation, improves water reuse and microalgae harvesting.